Preparation and Characterization of Poly (D,L-Lactide-Co-Glycolide) Microspheres for Controlled Release of KSL Peptide - Ahmed A. Hussein (College of Pharmacy University of Baghdad, 2017)
The purpose of this research was to prepare, characterize, and evaluate the new antimicrobial peptide  KSL peptide encapsulated in poly(D,L-lactide-co-glycolide) (PLGA)composite microspheres. KSL was loaded in poly(acryloyl hydroxyethyl) starch (acHES) micropar-ticles, and then the peptide-containing microparticles were encapsulated in the PLGA matrix by a solvent extraction /evaporation method.  KSL-loaded PLGA microspheres were also prepared without the starch hydrogel microparticle microspheres for comparison study. KSL peptide microspheres were characterized for drug content, surface morphology, microspheres size determination, polymers stability , in vitro microspheres degradation and in vitro release. KSL peptide encapsulation efficiency resulted in about 98% for RG503 microspheres and AcHES- RG503 composite microspheres. Microspheres mean diameters were 11.12Î¼m  and 28Î¼m for RG503 microspheres and AcHES- -RG503 composite microspheres respectively. Differential scanning calorimetry (DSC) analysis showed no structural changes in the polymers after KSL peptide loading.  The morphological effects and polymers degradation were analyzed to obtain a better understanding of the mechanism of KSL peptide release from microspheres and composite microspheres. Microspheres incubated in 0.1M phosphate buffer saline, pH 7.4 at 37Â°C were hydrated and started to degrade as shown by gel permeation chromatography (GPC) analysis. The result indicated that the release of KSL peptide from microspheres was due to the bulk degradation.  In vitro release profile showed that the microspheres type significantly affect the release of KSL peptide. In vitro KSL peptide release after 60 days incubation in 0.1M phosphate buffer saline, pH 7.4 at 37Â°C were 82.23% and 62.12% from 10% KSL peptide loaded AcHES-RG503 composite microspheres and 10%KSL peptide loaded RG503 microspheres respectively.   Key words :KSL peptide  , microspheres, composite microspheres,  PLGA